(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the implementation and impact of agricultural capital financing based on the Rahn Tasjily contract at the KSPPS BMT Al-Hikmah Semesta, Kaliaman Branch. The study used a qualitative descriptive approach with a case study method. Data collection techniques were carried out through field observations, in-depth interviews with managers and members receiving financing, and documentation related to the implementation of agricultural financing. Data were analyzed using interactive analysis techniques that include data reduction, data presentation, and drawing conclusions to obtain a comprehensive picture of the implementation of the Rahn Tasjily contract. The results of the study indicate that this financing helps farmers obtain business capital more easily without losing ownership of collateral assets. The financing is used to purchase seeds, fertilizers, and agricultural production inputs, thereby supporting increased productivity and farmer income. In addition, this sharia-based financing also helps reduce farmers’ dependence on loan sharks. However, the study found several obstacles, such as low sharia financial literacy, the risk of crop failure, fluctuations in commodity prices, and weak collateral legality. Therefore, it is necessary to strengthen education, risk management, and financing governance to ensure the sustainability of the program.